2001
DOI: 10.1038/ng792
|View full text |Cite
|
Sign up to set email alerts
|

Independent genome-wide scans identify a chromosome 18 quantitative-trait locus influencing dyslexia

Abstract: Developmental dyslexia is defined as a specific and significant impairment in reading ability that cannot be explained by deficits in intelligence, learning opportunity, motivation or sensory acuity. It is one of the most frequently diagnosed disorders in childhood, representing a major educational and social problem. It is well established that dyslexia is a significantly heritable trait with a neurobiological basis. The etiological mechanisms remain elusive, however, despite being the focus of intensive mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
268
7
6

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(293 citation statements)
references
References 20 publications
12
268
7
6
Order By: Relevance
“…20,21,27,29 Conversely, we found no evidence for linkage of phonological decoding accuracy (as measured by WA) or accuracy and speed (as measured by PDE) to locations on chromosomes 1p34-36 (DYX8), 2p16-15 (DYX3), 6p21.3 (DYX2), 11p15.5 (DYX7), 15q (DYX1), and 18p11 (DYX6) previously implicated in phonological decoding by others. For a complex and heterogeneous disorder, it is not surprising that different research groups have identified unique locations and have not always found supportive evidence for locations reported by others.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…20,21,27,29 Conversely, we found no evidence for linkage of phonological decoding accuracy (as measured by WA) or accuracy and speed (as measured by PDE) to locations on chromosomes 1p34-36 (DYX8), 2p16-15 (DYX3), 6p21.3 (DYX2), 11p15.5 (DYX7), 15q (DYX1), and 18p11 (DYX6) previously implicated in phonological decoding by others. For a complex and heterogeneous disorder, it is not surprising that different research groups have identified unique locations and have not always found supportive evidence for locations reported by others.…”
Section: Discussioncontrasting
confidence: 82%
“…In an earlier genome scan that identified a chromosome 18 location, there was also a discernible peak at D11S1314 at 79.5 cM for a composite measure of accuracy and speed of pseudoword reading using the DeFries-Fulker linkage analysis method (P ¼ 0.007) in a US sample. 27 That study also obtained P-values o0.01 for markers on chromosome 5p15 spanning the region identified in our study (D5S406 at 12.3 cM in the UK sample and D5S416 at 31.4 cM in the US sample) with measures of phonological decoding. Perhaps, it is the speed component of these phenotypes that is responsible for the signal.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The majority of families were recruited on the basis of having at least one proband whose single-word reading ability was > 2 s.d. below that predicted by tests of verbal or nonverbal reasoning 22,23 and where at least one sibling displayed evidence of DD. The remaining families were recruited through probands that were required to have single-word reading ability X1 s.d.…”
Section: Subjectsmentioning
confidence: 65%
“…All probands and siblings were administrated a battery of psychometric tests and we age-adjusted and standardized their scores against a normative control data set as previously described. 22,23 These included the following measures used in the present study for quantitative analysis: orthographic coding using irregular words (OC-irreg), phonological decoding ability (PD), orthographic coding assessed by a forced word choice test (OC-choice), single-word reading ability (READ), spelling ability (SPELL), phonemic awareness (PA), and tests of verbal (SIM) and nonverbal (MAT) reasoning. Multivariate linkage analysis had previously shown that the DYX2 QTL influenced variability shared by all the DD measures but did not influence IQ, 24 and univariate quantitative linkage analysis using IQ-adjusted traits refined the linkage signal.…”
Section: Subjectsmentioning
confidence: 99%